Comparison of Tooth Color Change After Bleaching With Conventional and Different Light-Activated Methods - Shahabi, Sima; Assadian, Hadi; Mahmoudi Nahavandi, Alireza; Nokhbatolfoghahaei, Hanieh (Journal of Lasers in Medical Sciences, 2017)
Introduction: The demand for esthetic dental treatments is increasing in recent years mainly due to improved oral hygiene and better maintenance of oral health and teeth in older individuals. Bleaching of discolored anterior teeth is the most popular among esthetic dental treatments. Even individuals with sound teeth and adequate esthetics seek to have whiter teeth in the anterior region. The aim of this study was to evaluate tooth color changes following conventional in-office bleaching techniques compared to light-activated methods using different light sources. Methods: Seventy sound anterior teeth (devoided of caries and/or fracture), extracted for periodontal and orthodontic reasons were selected and allocated to 7 groups: (A) control, (B) conventional bleaching (C) LED-activated bleaching, (D) KTP laser-activated bleaching, (E) diode laser-activated bleaching, (F) Nd:YAG laser-activated bleaching and (G) CO2 laser-activated bleaching. Colorimetric evaluation was carried out before and after treatment using a spectrophotoradiometer. Data were analyzed by one- and two-way analysis of variance (ANOVA) as well as multiple comparison methods. Results: The results showed that all bleaching procedures were effective in reducing the yellowness index. However, the KTP laser-activated bleaching was significantly more effective than the other techniques in 95% confidence level. It was also seen that CO2 laser activated method has outperformed groups E, F and G and the conventional bleaching without light activation was not effective at all and represented similar results with the control group. Furthermore, the groups E and G had almost the same results in decreasing the yellowness index. Conclusion: The results showed that all bleaching techniques were effective however, the KTP laser-activated bleaching was significantly more efficient, closely followed by the CO2 laser-activated bleaching technique.